Dis/ability studies: theorising disablism and ableism - Goodley, Dan (Routledge, 2014)
In this ground-breaking new work, Dan Goodley makes the case for a novel, distinct, intellectual, and political project – dis/ability studies – an orientation that might encourage us to think again about the phenomena of disability and ability. Drawing on a range of interdisciplinary areas, including sociology, psychology, education, policy and cultural studies, this much needed text takes the most topical and important issues in critical disability theory, and pushes them into new theoretical territory. Goodley argues that we are entering a time of dis/ability studies, when both categories of disability and ability require expanding upon as a response to the global politics of neoliberal capitalism. Divided into two parts, the first section traces the dual processes of ableism and disablism, suggesting that one cannot exist without the other, and makes the case for a research-driven and intersectional analysis of dis/ability. The second section applies this new analytical framework to a range of critical topics, including: The biopolitics of dis/ability and debility Inclusive education Psychopathology Markets, communities and civil society. Dis/ability Studies provides much needed depth, texture and analysis in this emerging discipline. This accessible text will appeal to students and researchers of disability across a range of disciplines, as well as disability activists, policymakers, and practitioners working directly with disabled people.
Keywords: EDI; approches et analyses; capacitisme; care; corps; cours; discipline; interdisciplinarité; lit4700; premier cycle; psychologie; pédagogie; santé; sciences de l'éducation; sciences humaines; sociologie; systèmes d'oppressions; thématiques; études culturelles

Handicap, recherche et changement social. L’émergence du paradigme émancipatoire dans l’étude de l’exclusion sociale des personnes handicapées - Boucher, Normand (Lien social et Politiques, 2003)
Le champ du handicap a subi de profondes transformations au cours des quatre dernières décennies dans la majorité des sociétés postindustrielles. Ce phénomène, qui influence les approches théoriques et la recherche à l’intérieur des sciences sociales, a fait surgir un nouveau paradigme émancipatoire basé sur une remise en cause des rapports entre le chercheur et le « sujet d’étude ». Dans cet article, nous explorons le développement de ce paradigme en nous appuyant sur l’expérience britannique, et nous discutons de son apport à la compréhension du handicap et des politiques sociales en abordant la question du rôle et de la position des acteurs au sein de la pratique de recherche
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; EDI; approches et analyses; capacitisme; corps; cours; discipline; histoire et politique; premier cycle; périodes historiques; ressource en ligne; ré; santé; sciences humaines; sex1920; sociologie; systèmes d'oppressions; thématiques; études critiques du handicap